PENERAPAN METODE PENEMUAN TERBIMBING DENGAN PENDEKATAN KONTEKSTUAL DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ARITMATIKA SOSIAL KELAS VII F SEMESTER GANJIL SMP NEGERI 1 RAMBIPUJI TAHUN AJARAN 2012/2013 - Arynda, A; Susanto, S; Dafik, D (KadikmA, 2012)
Abstract. Guided discovery method by contextual teaching is a learning way where students can find a concept with teacher guidence who motivates them to combine the knowledge taken from daily life. Beside that, it can also improve studentsâ activity and achievement in the teaching learning activity. The subject of the research is students of VII F grade of SMPN 1 Rambipuji. The data collection methods used in this research are documentation, observation, interview and test. The result of research showed that the increasing of studentsâ activity and achievement. The average percentage on the first cycle was 60,87 % and the second cycle was 72,54%. Whereas, the studentsâ average score of the last meeting in the first cycle was 74,49 and the second cycle was 81,24. The result also showed a good responses from the teacher and students. The good responses were proved by the increasing of studentsâ activity and achievement. Beside, there was also an effect on students thought between before and after teaching and learning process.Overall the guided discovery method by contextual teaching can improve studentsâ activity and achievement. Key Words : Guided discovery method by contextual teaching, studentsâ activity, achievement